2018
DOI: 10.1073/pnas.1715766115
|View full text |Cite|
|
Sign up to set email alerts
|

Heterogeneity within the frontoparietal control network and its relationship to the default and dorsal attention networks

Abstract: The frontoparietal control network (FPCN) plays a central role in executive control. It has been predominantly viewed as a unitary domain general system. Here, we examined patterns of FPCN functional connectivity (FC) across multiple conditions of varying cognitive demands, to test for FPCN heterogeneity. We identified two distinct subsystems within the FPCN based on hierarchical clustering and machine learning classification analyses of within-FPCN FC patterns. These two FPCN subsystems exhibited distinct pat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

40
280
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 438 publications
(349 citation statements)
references
References 100 publications
40
280
1
Order By: Relevance
“…In addition to interdigitated parallel networks, there are several fMRI studies demonstrating that the distributed large-scale networks occur in subportions across different mental states and tasks supporting the spatial reconfiguration observed over time in this study scenarios (Andrews-Hanna et al, 2010; Cole et al, 2013; Dixon et al, 2018; Leech et al, 2011). Furthermore, regarding default mode, intracranial electrophysiology studies demonstrate different patterns of activity across multiple regions of the default mode over time (for review please read (Fox et al, 2018)).…”
Section: Discussionsupporting
confidence: 80%
“…In addition to interdigitated parallel networks, there are several fMRI studies demonstrating that the distributed large-scale networks occur in subportions across different mental states and tasks supporting the spatial reconfiguration observed over time in this study scenarios (Andrews-Hanna et al, 2010; Cole et al, 2013; Dixon et al, 2018; Leech et al, 2011). Furthermore, regarding default mode, intracranial electrophysiology studies demonstrate different patterns of activity across multiple regions of the default mode over time (for review please read (Fox et al, 2018)).…”
Section: Discussionsupporting
confidence: 80%
“…Previous study has disclosed that the DAN is a goal‐directed cognitive control network that top‐down regulates responses to external stimuli (Corbetta & Shulman, ). Recent studies have also reported that the entire FPN is composed of three heterogeneous modules (namely, DMN aligned, DAN aligned, and dual aligned) that dissociably mediate global communication (Dixon et al, ; Spreng et al, ). This accords with the concept that the DAN globally regulates the positive networks by overseeing visuospatial encoding/planning (Spreng et al, ; Stawarczyk, Jeunehomme, & D'Argembeau, ), episodic retrieval, and WM (Luckmann, Jacobs, & Sack, ; Nee & Jonides, ).…”
Section: Discussionmentioning
confidence: 99%
“…In humans the frontoparietal and attention networks have been suggested to be dissociable into pairs of networks that are dissociable with respect to their functional proximity to unimodal versus transmodal systems (i.e. the default mode network) 53,54 . In our analysis, the FHI readily distinguished between the frontoparietal network-A (FN-A) and frontoparietal network-B (FN-B).…”
Section: The Cross-species Functional Homology Index (Fh Index)mentioning
confidence: 99%